Continuity and Change in the US–China–Taiwan Relations. (March 2020) - Hsieh, John Fuh-sheng
The relations between China and Taiwan (cross-Strait relations) have been a thorny issue for all parties concerned. These relations are one of the flashpoints in the world, which may trigger a serious military conflict. They involve not only China and Taiwan but also the United States. The purpose of this paper is to account for the trajectory of this triangular relationship with the help of opinion surveys in Taiwan. It is shown that when the Kuomintang (KMT) gains the governing power in Taiwan, Taiwan is the median voter in the cross-Strait relations game at the international level while as a non-traditional KMT or the Democratic Progressive Party is in power, it is the US that turns out to be the median voter.